ChemInform Abstract: Thermodynamic Studies of CaLaFe11O19(s). Issue 27 (13th June 2013) - Rakshit, S. K.; Parida, S. C.; Lilova, Kristina; Navrotsky, Alexandra
Abstract The title compound is thermodynamically characterized by Knudsen effusion mass spectrometry, calorimetry, and high temperature oxide melt solution calorimetry.